Technique Development in Improving the Solubility of Poorly Water Soluble Drugs (BCS II and IV): a Review Study: Pengembangan Teknik dalam Meningkatkan Kelarutan Obat yang Larut Buruk dalam Air (BCS Kelas II dan IV): Studi Review - Reza Pahlevi, Muhamad; Sopyan, Iyan; Gozali, Dolih (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Orally active drugs are currently available on the market. API should have adequate solubility and permeability to enhance its therapeutic efficacy when administered orally and obtain optimum bioavailability. Almost 40% of New Chemical Entities had limited solubility or fell into BCS class II and IV. Our review aims to summarize and discuss the development of methods and characterization for increasing the solubility of poorly aqueous drugs from papers published in Google Scholar, NCBI, Science direct, Researchgate, and MDPI. We checked that the methods used such as solid dispersion, cocrystal formation, and coamorphous can increase the solubility of API which has an impact on increasing bioavailability. The successful formation of solid dispersions, cocrystals and coamorphs can be confirmed by the characterization of PXRD, DSC and SEM. In conclusion, drug solubility is an important aspect of pharmacological effects. Drugs with high solubility can provide fast solubility rates and high bioavailability, reducing the dose administered. Solid dispersion, cocrystals, and coamorphous techniques, have succeeded in increasing the solubility of BCS class II and IV drugs.